Liver Diet in Hepatic Encephalopathy Patients - Choirina Windradi (SCITEPREES-Science and Technology Publications, Lda., 2017)
Hepatic encephalopathy (HE) is the most common complication, and one of the complicating manifestations of liver disease. Malnutrition is the most common complication of liver failure. Furthermore, it is a prognostic factor (survival rate, length of stay in hospitals and life quality) in cirrhosis patients. The primary concept of HE pathogenesis is intestine-derived nitrogen compounds that affect brain function. Daily protein intake is a key in HE pathogenesis; therefore, HE patients need nutrient intake in addition to medication